Exploring associations between pregnancy cravings and sociodemographic, lifestyle and health factors: insights from a cross-sectional population study in Jordan - Suad M Kloub; Saleem A Banihani (BMJ Open)
Objective To explore the potential associations between pregnancy cravings and various sociodemographic, lifestyle and health factors.Design Cross-sectional study.Setting Population-based study in Jordan.Participants A total of 500 women who had children and experienced pregnancy cravings were included.Primary and secondary outcome measures Pregnancy cravings are prevalent among Jordanian women and associated with some sociodemographic, lifestyle and health factors.Results The results showed that 75.40% (377/500) of women experienced food cravings, with 40.6% and 29.1% of them having iron deficiency and vitamin D deficiency, respectively. The most commonly craved food items were sweets (17.2%, 86/500) and salts (22.2%, 115/500), while less than 1.0% of women craved non-food items. No significant correlation (p>0.05) was found between food cravings and the gender of the babies. Significant associations were found between food cravings and the mother’s educational level (p=0.023), weight loss (p<0.001) and diseases such as anaemia (p=0.01).Conclusion Pregnancy cravings, particularly for food items, with sweets and salts being the most commonly craved, are prevalent among Jordanian women and are associated with the mother’s educational level, changes in weight and the presence of anaemia. Additionally, the study found that iron and vitamin D deficiencies are prevalent health issues among women experiencing these cravings in Jordan. This research has important implications, emphasising the pressing need for targeted nutritional interventions and healthcare strategies to address identified deficiencies and improve maternal health outcomes in the region.